The Effect of Distance on Moral Engagement: Event Related Potentials and Alpha Power are Sensitive to Perspective in a Virtual Shooting Task - Petras, Kirsten; ten Oever, Sanne; Jansma, Bernadette M. (Frontiers in Psychology, 2016)
In a shooting video game we investigated whether increased distance reduces moral conflict. We measured and analyzed the event related potential (ERP), including the N2 component, which has previously been linked to cognitive conflict from competing decision tendencies. In a modified Go/No-go task designed to trigger moral conflict participants had to shoot suddenly appearing human like avatars in a virtual reality scene. The scene was seen either from an ego perspective with targets appearing directly in front of the participant or from a bird's view, where targets were seen from above and more distant. To control for low level visual features, we added a visually identical control condition, where the instruction to “shoot” was replaced by an instruction to “detect.” ERP waveforms showed differences between the two tasks as early as in the N1 time-range, with higher N1 amplitudes for the close perspective in the “shoot” task. Additionally, we found that pre-stimulus alpha power was significantly decreased in the ego, compared to the bird's view only for the “shoot” but not for the “detect” task. In the N2 time window, we observed main amplitude effects for response (No-go > Go) and distance (ego > bird perspective) but no interaction with task type (shoot vs. detect). We argue that the pre-stimulus and N1 effects can be explained by reduced attention and arousal in the distance condition when people are instructed to “shoot.” These results indicate a reduced moral engagement for increased distance. The lack of interaction in the N2 across tasks suggests that at that time point response execution dominates. We discuss potential implications for real life shooting situations, especially considering recent developments in drone shootings which are per definition of a distant view.